1988
DOI: 10.1902/jop.1988.59.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Root Curettage and Gingival Repair in Periodontitis

Abstract: Twelve patients, aged 35 to 60, having adult Periodontitis were treated with scaling and root planing performed with ultrasonic and hand sealers. Biopsies were taken, gingival crevicular fluid and clinical parameters were analyzed at different times, and the healing process was monitored. Findings showed a clear correlation between the amount of crevicular fluid and the histological inflammatory pattern, whereas no relationship between crevicular fluid and gingival pocket depth was apparent. In this study, no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…This was evidenced by lower Gingival Index scores and BoP+ values (Fig. 2) and confirms data previously reported (Ramfjord & Kiester 1954, Moskow 1962, 1964, Biagini et al 1988, Boretti et al 1995). The most important observation made in the current model study was, however, that there was a significantly larger proportion of test than control sites that after 1 and 2 weeks of healing had reached the predetermined endpoint of success in terms of resolution of inflammation (Tables 2, 3).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was evidenced by lower Gingival Index scores and BoP+ values (Fig. 2) and confirms data previously reported (Ramfjord & Kiester 1954, Moskow 1962, 1964, Biagini et al 1988, Boretti et al 1995). The most important observation made in the current model study was, however, that there was a significantly larger proportion of test than control sites that after 1 and 2 weeks of healing had reached the predetermined endpoint of success in terms of resolution of inflammation (Tables 2, 3).…”
Section: Discussionsupporting
confidence: 92%
“…It was observed that subgingival instrumentation (i) produced injury to the sulcus epithelium and adjacent connective tissue, but also that (ii) re‐epithelialization of the sulcus occurred and a diminished “inflammatory reaction in the gingival corium” took place within 7 days after instrumentation. A detailed examination of gingival tissue repair following non‐surgical periodontal therapy was performed by Biagini et al (1988). 12 patients with chronic periodontitis participated in the study.…”
mentioning
confidence: 99%
“…The first study showing that there was no difference between manual applications and ultrasonic devices in terms of the activity was done by Badersten et al [11] and then it was supported by so many studies [11][12][13][14][15][16][17][18]. It was agreed that sonic and ultrasonic devices provided similar clinical results with the scaling and root planning process in the American Academy of Periodontology 1996 world workshop' [14].…”
Section: Discussionmentioning
confidence: 98%
“…Treatment duration with β-glucan varies from 39 days to 90 days in animal and human studies according to the type and severity of the problem (Breivik et al,2005;Kabasakal et al, 2011;Lin et al, 2011;Sarinho et al, 2009;Turunen et al, 2011). Biagini et al (1988) documented soft tissue healing after NPT and found precisely oriented collagen bundle fibres by 30 days to 60 days. Furthermore, Magnusson et al (1984) reported that repopulation of subgingival microbiota occurred between 30 to 60 days.…”
Section: Discussionmentioning
confidence: 99%